Asset booms and fat tails in East Asia symmetric or asymmetric risks? Maria Socorro Gochoco-Bautista,. - Bautista, Maria Socorro Gochoco
Do housing and equity booms significantly raise the probability at the margin of the realization of extreme outcomes in output and prices, and are the worst outcomes just as likely to occur as the good ones? This study addresses these questions for a group of eight East Asian countries. The risk of extreme outcomes occurring is measured by the probability of being in the tails of a distribution. The distributions of real output-and price level-gaps exhibit fat tails, in which the probability and size of the worst possible outcomes are higher than if the distribution were normal. Expected real output- and price level-losses from asset booms would therefore be larger than suggested by the normal distribution if asset price booms significantly raise the risk of extreme outcomes occurring. The main findings are that (i) asset price booms in housing and equity markets, but especially in housing, significantly raise the probability at the margin that real output- and price level-gaps will be in the tails of worst outcomes of their respective distributions and (ii) the risks arising from asset booms are not symmetric-only particularly bad outcomes are more likely. The implication for monetary policy is that an approach that is ex-ante more compatible with risk management may be appropriate.
Keywords: Asset-backed financing -- East Asia; Monetary policy -- East Asia